2007
DOI: 10.1007/s00586-007-0304-3
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic intratumoural haemorrhage: an unusual presentation of spinal ependymoma

Abstract: Ependymomas presenting with intratumoural and/or subarachnoid haemorrhages are seen rarely. These haemorrhages are mostly due to anticoagulation, epidural analgesia or pregnancy. A 62-year-old male farmer with cauda equina syndrome after a work-related trauma is presented. He was admitted to our hospital with paraparesis, faecal incontinance and sensory loss below the level of the lumbar-2 dermatome. Magnetic resonance imaging of the spine displayed an intradural mass lesion at the level of the first lumbar ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(8 reference statements)
0
4
0
2
Order By: Relevance
“…Otros síntomas habituales son parestesias en miembros inferiores y alteraciones esfinterianas 20 . En la literatura existen numerosas referencias en relación con distintas formas de presentación en los ependimomas de esta localización: como hemorragias intratumorales espontáneas o traumáticas 2,25 , hemorragia subaracnoidea 35, el desarrollo de una hidrocefalia comunicante 42 , probablemente en relación con microsangrados asintomáticos o al incremento de las proteínas en el líquido cefalorraquídeo, como ya ha sido publicado en otros tumores medulares. La duración de la sintomatología previa al diagnóstico se ha reducido progresivamente desde la introducción de la RM en el diagnostico de la patología raquimedular.…”
Section: Discussionunclassified
“…Otros síntomas habituales son parestesias en miembros inferiores y alteraciones esfinterianas 20 . En la literatura existen numerosas referencias en relación con distintas formas de presentación en los ependimomas de esta localización: como hemorragias intratumorales espontáneas o traumáticas 2,25 , hemorragia subaracnoidea 35, el desarrollo de una hidrocefalia comunicante 42 , probablemente en relación con microsangrados asintomáticos o al incremento de las proteínas en el líquido cefalorraquídeo, como ya ha sido publicado en otros tumores medulares. La duración de la sintomatología previa al diagnóstico se ha reducido progresivamente desde la introducción de la RM en el diagnostico de la patología raquimedular.…”
Section: Discussionunclassified
“…There are numerous references in the literature regarding various atypical forms of presentation in ependymomas, [11,14]. One of our patients was diagnosed with a pseudovascular form, which clinically presented an acute myelopathic syndrome due to tumor bleeding, as evidenced by MRI.…”
Section: Discussionmentioning
confidence: 88%
“…From the histopathological point of view, we found that the myxopapillary group at the level of the terminal phylum was the most frequent. On the other hand, the less frequent histological subtype was the anaplastic with dorsal localization [14][15][16][17][18]. The most important and effective treatment of intraspinal ependymomas is surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otros síntomas habituales son parestesias en miembros inferiores y alteraciones esfinterianas 20 . En la literatura existen numerosas referencias en relación con distintas formas de presentación en los ependimomas de esta localización: como hemorragias intratumorales espontáneas o traumáticas 2,25 , hemorragia subaracnoidea 35, el desarrollo de una hidrocefalia comunicante 42 , probablemente en relación con microsangrados asintomáticos o al incremento de las proteínas en el líquido cefalorraquídeo, como ya ha sido publicado en otros tumores medulares.…”
Section: Discussionunclassified